2021
DOI: 10.1096/fj.202100782rr
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor‐1β shapes the energetic homeostasis of kidney tubule cells

Abstract: Energetic metabolism controls key steps of kidney development, homeostasis, and epithelial repair following acute kidney injury (AKI). Hepatocyte nuclear factor-1β (HNF-1β) is a master transcription factor that controls mitochondrial function in proximal tubule (PT) cells. Patients with HNF1B pathogenic variant display a wide range of kidney developmental abnormalities and progressive kidney fibrosis. Characterizing the metabolic changes in PT cells with HNF-1β deficiency may help to identify new targetable mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Secondly, in vitro and in vivo experiments have shown that HNF1β controls mitochondrial respiration in the PT [ 15 , 61 ]. Inhibition or KO of HNF1β in a human PT cell line resulted in either downregulation of Ppargc1a (important for mitochondrial biogenesis) and altered mitochondrial morphology or ATP reduction and increased glycolysis, respectively [ 15 , 61 ]. The kidney requires large quantities of ATP to maintain electrochemical gradients across membranes which are particularly important for transcellular ion transport [ 9 ].…”
Section: Mechanisms Of Disturbed Electrolyte Transport In Adtkd-hnf1β...mentioning
confidence: 99%
“…Secondly, in vitro and in vivo experiments have shown that HNF1β controls mitochondrial respiration in the PT [ 15 , 61 ]. Inhibition or KO of HNF1β in a human PT cell line resulted in either downregulation of Ppargc1a (important for mitochondrial biogenesis) and altered mitochondrial morphology or ATP reduction and increased glycolysis, respectively [ 15 , 61 ]. The kidney requires large quantities of ATP to maintain electrochemical gradients across membranes which are particularly important for transcellular ion transport [ 9 ].…”
Section: Mechanisms Of Disturbed Electrolyte Transport In Adtkd-hnf1β...mentioning
confidence: 99%
“…Among the transcription factors responsible for those changes, HNF1b is inextricably linked to kidney health (8). It plays a role in fetal development, ion transport and mitochondrial health, while human mutations of HNF1b result in various nephropathies (9, 10, 11, 12). Taken together, those insights into renal enhancer activity open new avenues of investigation, as in some cases, the usual gene deletion approach is not viable to dissect the gene’s role, and reducing gene expression through enhancer deletion can provide new understanding of clinically relevant mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…8 It plays a role in fetal development, ion transport and mitochondrial health, while human mutations of HNF1b result in various nephropathies. [9][10][11][12] Taken together, those insights into renal enhancer activity open new avenues of investigation, as in some cases, the usual gene deletion approach is not viable to dissect the gene's role, and reducing gene expression through enhancer deletion can provide new understanding of clinically relevant mechanisms.…”
Section: Introductionmentioning
confidence: 99%